Effects of Cooperative Learning Model in Science Learning on Students’ Cognitive and Critical Thinking Ability: A Meta Analysis - Frima Triani; Rissa Praminta; Halimah Tusa’diah; Suci Ana Yolanda (Universitas Negeri Padang, 2023)
Learning requires students to be able to improve the various abilities needed in the 21st century. However, student abilities were still low. The solution to the problem is to apply a cooperative learning model. This study aims to determine the effect of using the cooperative model on students' knowledge abilities and critical thinking skills in science learning which is determined through the effect size. This study uses a descriptive meta-analysis research method. Research data were obtained from 20 journals about the effect of using the cooperative learning model, where there were 10 journals related to learning outcomes and 10 journals on students' critical thinking skills. Research is based on two categories, the ability achieved and the type of cooperative learning model. The results showed that the use of the cooperative model in the category of student ability obtained an average effect size of 0.93 high category on learning outcomes and an average effect size of 1.08 high category on critical thinking skills which showed a positive influence in improving student abilities. Second, based on the type of cooperative learning model, the average effect size is 0.74 in the medium category, which indicates that the use of cooperative learning models is still less effective in improving student learning outcomes. The average effect size value for critical thinking skills which shows the type of cooperative learning model is 0.76 has a positive effect on students' critical thinking skills. Therefore, it is important for educators to use learning models to improve students' skills.